Dinamika Sosial Gerakan Guru di Indonesia Pasca Orde Baru - Rakhmat Hidayat (Jurnal Pendidikan dan Kebudayaan, 2011)
This article aims is to: 1) describes the dynamics of movement of teachers in Indonesia after New Order era. This phase is marked by the emerging various teacher organizations in Indonesia and 2) explain how the contribution of Indonesian teachers movement in the stage of democracy in Indonesia. There are two important conclusions in this paper are 1) Indonesian teacher movement that developed after the New Order era is the manifestation and articulation of a political system that supports the emergence of these movements; 2) the movement of Indonesian teachers become an important social group in the transition to democracy in Indonesia after New Order. The methodology used is the study of literature by examining a variety of related references teachersâ€™ movement in Indonesia. Movement of teachers in Indonesia have to do the strengthening and consolidation of networks both national and international networks. Their movements will be more solid, structured and institutionalized as an important actor in the transition to democracy in Indonesia.Â ABSTRAKTujuan penulisan artikel ini yaitu: 1) menjelaskan dinamika gerakan guru Indonesia setelah era Orde Baru. Fase ini ditandai dengan bermunculan berbagai organisasi guru di Indonesia dan 2) menjelaskan bagaimana kontribusi gerakan guru Indonesia dalam pentas demokrasi Indonesia. Ada dua kesimpulan penting dalam tulisan ini yaitu: 1) gerakan guru Indonesia yang berkembang setelah era Orde Baru merupakan manifestasi dan artikulasi dari sistem politik yang mendukung munculnya gerakan tersebut; 2) gerakan guru Indonesia menjadi kelompok social penting dalam transisi demokrasi di Indonesia setelah Orde Baru. Metodologi yang digunakan adalah kajian literature dengan mengkaji berbagai referensi terkait gerakan guru di Indonesia. Hal penting yang harus dilakukan oleh gerakan guru di Indonesia adalah melakukan penguatan dan konsolidari jaringan baik jaringan nasional maupun internasional. Dengan cara ini gerakan mereka akan lebih solid, terstruktur dan terlembagakan sebagai actor penting dalam transisi demokrasi di Indonesia.